2022
DOI: 10.3390/biomedicines10123095
|View full text |Cite
|
Sign up to set email alerts
|

Black Garlic and Thiosulfinate-Enriched Extracts as Adjuvants to Ceftriaxone Treatment in a Rat Peritonitis Model of Sepsis

Abstract: To date, there have been no new drugs or adjuvants able to decrease both morbidity and mortality in the context of sepsis and septic shock. Our objective was to evaluate the use of thiosulfinate-enriched Allium sativum and black garlic extracts as adjuvants in the management of sepsis. An experimental in vivo study was carried out with male Sprague–Dawley® rats. Animals were randomized in four treatment groups: antibiotic (ceftriaxone) treatment (group I), ceftriaxone plus thiosulfinate-enriched extract (TASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In a previous study, using the same TASE as a adjuvant, we found TASE reduced inflammation in a rat peritonitis sepsis model [ 17 ]. We found different results when we evaluated the effects of TASE on the human monocyte response.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In a previous study, using the same TASE as a adjuvant, we found TASE reduced inflammation in a rat peritonitis sepsis model [ 17 ]. We found different results when we evaluated the effects of TASE on the human monocyte response.…”
Section: Discussionmentioning
confidence: 88%
“…Allium sativum has traditionally been associated with beneficial effects in infectious processes due to its antimicrobial, anti-inflammatory, and antioxidant properties [ 6 , 17 , 31 , 32 ]. However, it has not yet been introduced in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations